Pengaruh Promosi di Media Sosial dan Electronic Word-of-Mouth Terhadap Minat Kunjungan ke Telaga Biru Cicerem, Kuningan, Jawa Barat - Lionika Roselie; Myrza Rahmanita; Sri Mariati (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2022)
Marketing attracts consumers' attention and desires to make interesting visits. Electronic Word-of-Mouth also supports consumer interest in visiting because it contains interesting information about tourist attractions and reviews from other tourists. This study aims to explain the effect of social media promotion and electronic word-of-mouth on visiting interest. This study aims to (1) determine the effect of social media promotion on interest in visiting Telaga Biru Cicerem, Kuningan, West Java, (2) The effect of electronic word-of-mouth (e-WOM) on interest in visiting Telaga Biru Cicerem, Kuningan, Java. . West (3) The effect of social media promotion and electronic word-of-mouth on interest in visiting Telaga Biru Cicerem, Kuningan, West Java. Therefore, it is recommended that BUMDES Telaga Biru Cicerem continue to increase the quantity of brand image-based media updates and maintain a brand image that is marked as the best tourist destination information to increase interest in visiting Telaga Biru Cicerem.